The archive oh historical materials in digital era as cultural value - Santos Silva, A. (2017)
Documenting and preserving materials data is important both to fulfill researcher’s needs and to obtain social benefits concerning the related educational and historical value. The samples repository is also demanded as a basis for further understanding, innovation and development, besides the preservation of the materials historical value and information. The dissemination of those materials importance to non-specialized interested publics may also be enhanced by a database. DB-HERITAGE project (Database of building materials with historical and heritage interest) discusses in this paper the meaning of the archive as a cultural value that is established from the relationship between tangible (physical archive) and intangible (digital archive). Reflecting on the archive of historical materials as a heritage value, it is pointed out its significance for the valorization of the architectural heritage